Spatiotemporal analysis of groundwater level trends and recharge rate estimation in the unconfined aquifer of Yogyakarta-Sleman Groundwater Basin, Indonesia - Razi, Muhammad Haikal; Wilopo, Wahyu; Putra, Doni Prakasa Eka (Journal of Degraded and Mining Lands Management, 2023)
Groundwater is the primary water resource used for domestic, industrial, and agricultural needs for the community in the Yogyakarta-Sleman Groundwater Basin area. The urbanization rate has increased since the 1970s and has made massive use of groundwater, causing environmental problems, including the quality and quantity of groundwater. Therefore, this study aimed to investigate the spatiotemporal groundwater fluctuation trends based on the non-parametric Mann-Kendall test and recharge rate estimation using the water table fluctuation (WTF) method. The groundwater level data were collected from monitoring wells across the study area during 2018-2022, particularly emphasizing 8 wells representing recharge, transition, and discharge areas. The results showed that the groundwater fluctuation pattern generally followed the season. During the rainy season from January to April, groundwater reached the shallowest level and began to decline gradually when it entered the dry season from May to October. Groundwater recharge rate was estimated to vary from 171.49 to 1,505.56 mm/year. Meanwhile, the Mann-Kendall test showed that most of the Yogyakarta-Sleman Groundwater Basin area did not experience significant fluctuation trends, except for two monitoring wells in the center of Yogyakarta City which had increasing groundwater level trends. The rising groundwater levels were expected to be caused by urban wastewater recharge. This study has provided a new description and insights into spatiotemporal changes in the groundwater table and the quantification of groundwater recharge.